Towards a green post-crisis economy? - The position of Finland in environmental technologies - Christopher Palmberg; Tuomo Nikulainen (The Research Institute of the Finnish Economy (ETLA), 2010)
Climate change is a major global challenge and governments around the world are now promoting environmental technologies to address both climate change and realize new employment and growth opportunities in this rapidly expanding area. Investments have reached unprecedented levels and stimulus packages to tackle the recent economic crisis also contain noticeable commitments to green technologies. Innovation policies are now under pressure to capitalize these investments and define priorities in the application of environmental technologies to both boost competitiveness and eco-innovation. The aim of this paper is to clarify foreseen impacts of growing environmental technology investments, 'green' components of economic stimulus packages and the ideas of a 'Global Green New Deal' and 'Green Growth' and to assess how Finland is positioned in environmental technologies. The paper reviews existing studies, analyzes global and Finnish patenting and considers the role of environmental technologies in its industrial context in Finland. The findings suggest that renewable energy is the most rapidly expanding environmental technology area, while the economic stimulus packages will play a lesser role than originally anticipated in transitions to low-carbon economies. Finland is comparatively well positioned in environmental technologies by overall levels of patenting activity. Nonetheless, Finland does not have a specific specialization profile in the area, neither a comparative advantage in renewable energy technologies as the most rapidly expanding fields globally. Environmental technologies are developed in the context of a broad range of Finnish industries whereby the application potentials of these technologies are manifold.
Keywords: 330; environmental technologies; 'Global Green New Deal'; 'Green Growth'; investments; patenting; Finland